A COMPARISON OF METHODS FOR CALCULATING LACTATE ANAEROBIC THRESHOLDS IN JUDO AND MIXED MARTIAL ARTS ATHLETES - Gabrys, Tomasz Tytus; Stanula, Arkadiusz; Szmatlan-Gabryś, Urszula (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The study aimed to determine the differences between exercise intensities at the anaerobic threshold values (VAT) calculated with methods of lactate curve analysis such as LTvisual, LTloglog, LT4.0, LTΔ1, and LTD-max, and to build regression equations that allow athletic training specialists to compare VAT values obtained from LTvisual, LTloglog, LTΔ1, LTD-max with that calculated with LT4.0. The sample analysed during the study consisted of 19 judoka and 22 MMA practitioners in a preparation period for competition. Each of the two disciplines has its own hierarchy of VAT values. The analysis aimed to determine the effect of the athletic discipline factor and of the method factor on VAT values. Results: The coefficient of variation (CV) values obtained indicate that the effective exercise intensities have bigger variation in judoka aerobic endurance training. VAT values assessed for judoka using different methods for analysing the blood lactate concentration curve are more consistent than in MMA competitors. Conclusions: Judo and MMA competitors have their specific hierarchies of running velocities at the anaerobic threshold, with both the athletic discipline factor and the method factor having an interaction effect on the VAT level. VAT levels assessed from the different methods used to analyse the blood lactate concentration curve are more consistent (ANOM) in judoka than in MMA practitioners.